User Name Remember Me? Password

 Algebra Pre-Algebra and Basic Algebra Math Forum

 April 5th, 2014, 11:11 PM #1 Senior Member   Joined: Nov 2013 Posts: 434 Thanks: 8 log (3x)^log3 =(5y)^log5 x^log5 = y^log3 April 5th, 2014, 11:22 PM #2 Senior Member   Joined: Jul 2010 From: St. Augustine, FL., U.S.A.'s oldest city Posts: 12,211 Thanks: 521 Math Focus: Calculus/ODEs What have you tried? April 5th, 2014, 11:40 PM   #3
Senior Member

Joined: Apr 2013

Posts: 425
Thanks: 24

Quote:
 Originally Posted by mared (3x)^log3 =(5y)^log5 x^log5 = y^log3
If it is a system of equations, then apply the "" of the two equations and you'll get a system of equations with the unknowns and .

Last edited by skipjack; April 6th, 2014 at 05:39 AM. April 6th, 2014, 05:47 AM #4 Global Moderator   Joined: Dec 2006 Posts: 21,019 Thanks: 2253 The first equation is satisfied by (x, y) = (1/3, 1/5) or (x, y) = (0, 0). What about the second? April 6th, 2014, 05:03 PM   #5
Math Team

Joined: Dec 2006
From: Lexington, MA

Posts: 3,267
Thanks: 408

Hello, mared!

I'll get you started . . .

Quote:
 $\displaystyle \begin{array}{cccc}(3x)^{\log3} &=& (5y)^{\log5} &  \\ x^{\log5} &=& y^{\log3} & \end{array}$

Take the log of equation :

$\displaystyle \;\;\;\begin{array}{cc}\log(3x)^{\log3} \:=\:\log(5y)^{\log5} \\ \log3\log(3x) \;=\;\log5\log(5y) \\ \log3(\log3 + \log x) \;=\;\log5(\log5+\log y) \\ (\log3)^2 + \log3\log x \;=\;(\log5)^2 + \log5\log y \\ \log3\log x - \log5\log y \;=\;(\log5)^2 - (\log3)^2 & \end{array}$

Take the log of equation :

$\displaystyle \;\;\;\begin{array}{cc}\log\left(x^{\log5}\right) \;=\;\log\left(y^{\log3}\right) \\ \log5\log x \;=\;\log3\log y \\ \log5\log x - \log3\log y \;=\;0 &  \end{array}$

$\displaystyle \text{Let: }\:\begin{Bmatrix}a \,=\,\log3 \\ b \,=\,\log5 \end{Bmatrix}\quad \begin{Bmatrix}X \,=\,\log x \\ Y \,=\,\log y \end{Bmatrix}$

$\displaystyle \text{Then  and  become: }\:\begin{Bmatrix}aX - bY &=& b^2-a^2 \\ bX - aY &=& 0 \end{Bmatrix}$

Solve the system and back-substitute. April 6th, 2014, 05:55 PM #6 Senior Member   Joined: Mar 2014 Posts: 112 Thanks: 8 The second equation is satisfied by (x, y) = (1, 1) or (x, y) = (0, 0). Tags log Thread Tools Show Printable Version Email this Page Display Modes Linear Mode Switch to Hybrid Mode Switch to Threaded Mode

 Contact - Home - Forums - Cryptocurrency Forum - Top      